Bridging innovation and commercialization to create value: An open innovation study - Wang, Yun-chu; Phillips, Fred; Yang, Chyan (Journal of business research, 2021)
•ITRI has achieved end-to-end open innovation resulting in many successes of commercialization.•The four-platform open innovation system is a usable framework to bridge innovation and commercialization.•Key success factors are a neutral internal coordinating organization and an external advisory board of investors. The paper demonstrates how ITRI (the Industrial Technology Research Institute), an internationally prominent non-profit R&D organization, designs a platform-based open innovation system to capitalize on its efforts toward creating economic and social value. We illustrate a holistic framework spanning idea generation to commercialization, and present successful ITRI cases. Detailed actionable descriptions of activities in each innovation stage illustrate the operational implementation of the end-to-end open innovation system. We find distinctive success factors: (1) Managers examine their open innovation strategies and activities by viewing the open innovation process from a system perspective. (2) Outside and inside advisors with investment backgrounds help commercialization planning. (3) A neutral catalyst organization within ITRI is a critical player, maintaining the smooth flow of the end-to-end process. Our findings provide important implications for research and management in open innovation as well as for the systematic commercialization of innovation.